ILTEL: iluminação temática a LED - Valle, Danillo do (2013)
The proper match of elements such as decoration, music and lighting is one of the key-factors for a successful event. Lighting system is no longer a simple detail, it plays a special role in all sorts of events, always attracting attention in a positive way of its participants. The Thematic LED Lighting platform (ILTEL), developed in this graduation project, consists of a backlit floor by an array of microcontrolled RGB LEDs and of an easy to operate software for managing visual content from a PC. Its simple operation allows user to select the content to be displayed in real time, providing a dynamic interaction between the environment and ILTEL. It can be used as a complement to an already existing lighting system or become the main element of lighting system, creating an innovating and dynamic environment. About the light source used, it is emphasized that the LEDs provide lower power consumption compared to conventional sources, implying indirectly in reducing CO2 emissions, they have long life due to no moving parts and dissipate little power, and also are compatible with international standard Restriction of Certain Hazardous Substances (RoHS), once its disposal bring little impact to the environment. The current ILTEL version uses USB communication between the PC and the controller boards of LEDs array. The controller boards are ARM microcontroller based and activate the LEDs of the matrices. Two arrays of 32x32 LEDs are controlled, operating at a frequency (refresh rate) of 60 Hz. The developed architecture allows easy expansion of the panel dimensions by the inclusion of controller boards and LED arrays.